Development of a Desktop PCB Milling Machine - Azmi, Nur Amirah Hanim; Ayob, Mohammad Afif; Rohaziat, Nurasyeera (Evolution in Electrical and Electronic Engineering, 2022)
Conventional desktop PCB milling machines cost about 3000 on average, while machines with an onboard liquid crystal display (LCD) for the user interface are nearly non-existent. To address this issue, a desktop PCB milling machine with an embedded LCD display is proposed. Users can save several files on the secure digital (SD) card, tweak the machine on the go, and make the machine work without needing to connect to a computer. This milling machine has three axes and was designed in the same way as a 3D printer. SolidWorks was used to design the machine’s structure before being 3D printed while Marlin v2.0.7.2 firmware was used to control the movement. A prototype model was developed to evaluate and verify the design and the findings revealed a 0.2% percentage error between the actual and measured gantry movement.